The Nicaraguan Caribbean Coast: Melting pot and amalgam - Rossman-Tejada, Yolanda Elizabeth (2022)
Through this essay, I intend to share a brief reflection from my personal experience through poetry, on how literary creation and the multiculturalism of the land where I was born, have an impact on me, sailing among seas of diverse tonalities but that in the end, have shown me that they emerge from the same ancestral source beyond the skin, language, customs, religions and the territories we inhabit.  There are more common elements that as human beings guide us towards shared utopias. As a woman writer, I interpret the world in which we live and coexist, naming things, evidencing them, and spreading them in order to influence the transformations we seek. For this essay I base my work mainly on personal experiences, in addition to research carried out in documentary sources related to the subject and information gathered from interviews with my paternal grandfather and my father, both now deceased. They were of vital importance to mark the route to follow in this process, which decodes the intricacies of my genealogy; a curiosity that deepened when I began my master's studies in social anthropology in 2004, when I concluded that I am a melting pot and an amalgam.